MISTISISME DALAM NOVEL RITUAL SETAN KARYA DIOSETTA: KAJIAN TEORI NIELS MULDER - Putri Marshanda Khumairoh; Resdianto Permata Raharjo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the existence, stages of development, and motifs of mysticism in the novel Ritual Setan by Diosetta, utilizing the framework of Niels Mulder's mysticism theory. The research method employed is descriptive qualitative with a content analysis approach. The primary data source is the text of Diosetta's novel Ritual Setan, while data collection techniques involved library research and close reading. The results indicate that the existence of mysticism manifests as dark mysticism, which is realized through material aspects (magical objects, offerings, sacrifices), spiritual aspects (apparitions of supernatural entities and shifts in inner consciousness), and moral aspects (degradation of human values). Furthermore, the characters' mystical journey undergoes a radical deviation from the sacred essence of Javanese spirituality across Mulder's four stages (sarengat, tarekat, hakekat, makripat), culminating in a destructive spiritual bond and incestuous rituals. This deviation is primarily driven by the dominance of egoistic motifs (the instant pursuit of material wealth and social status). Conversely, positive motifs emerge as a counterbalancing force through ascetic practices, prayers, and the moral recovery process of the main character. This study concludes that the novel Ritual Setan serves as a sharp cultural critique of the spiritual crisis faced by modern humans trapped in the current of materialism Keywords: Mysticism, Niels Mulder's Theory, Ritual Setan, Pesugihan, Contemporary Literature.